Efektifitas Metode Pembelajaran Brainstorming Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas VII SMP Negeri 7 Baubau - Herlawan Herlawan; Abdurahman Askois; Nursinta Yani (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2023)
The formulation of the problem in this study was whether the Brainstorming learning method is effective on the mathematical problem solving abilities of class VII students of SMP Negeri 7 Baubau. The purpose of this study was to find out whether the Brainstorming learning method was effective on the math problem solving abilities of class VII students of SMP Negeri 7 Baubau. This type of research is Quasy Experiment. The population in this study were all students of class VII SMP Negeri 7 Baubau in 3 classes with a total of 85 students. The sample in this study consisted of 2 classes, namely class VII A which consisted of 27 students as the control class. Data collection techniques in this study used test. Data analysis techniques used in this study were descriptive analysis and inferential analysis in the form of t-test. Based on the research results obtained: the average problem solving ability of experimental class students was 77.96; the average problem-solving ability of control class students is 68.70; based on the results of hypothesis testing using the t test, the value of tcount is 2.448. For ttable values at significance level of 0.05 (5%) and df = 52, namely 2.006. Based on this value tcount > ttable then H1 is accepted. So, the data concluded that Brainstorming learning method was effective on the math problem solving abilities of class VII students of SMP Negeri 7 Baubau.